HERMENEUTIKA: ARAH BARU INTERPRETASI HADIS (Studi Analisis Pemikiran Yusuf al-Qardhawi dalam Fatwa-fatwanya) - Izza, Farah Nuril (Fakultas Dakwah IAIN Purwokerto, 2014)
The hermeneutics issues as an alternative interpreting method is a new concern in Islamic World; however its application has existed since long time ago. Generally, Hermeneutics in the religious context especially in Al Qurâ€™an and Al Hadits has a specific purpose to find out the original meaning from a text by using it in the socio-historical context. Yusuf Qardhawi as one of contemporary scholars takes â€œin betweenâ€ position in comprehending Hadits or Sunnah. He applies basic principles, characteristics, and essential rules to study it appropriately. He also is considered as a representative from the reformers who contribute their thoughts for Islamic development in order that the religious texts can be more harmonious along with time development but they donâ€™t lose their authenticity. Qardhawiâ€™s methodology of hermeneutics thought in Hadits always connects between norma tive texts as the law source and their historicity in the socio-historical context in the local muslim community. He sets out his ideas and purposes from the texts of hadits themselves and the tools and applications are adapted with the sociohistorical context of local community.